2013
DOI: 10.1097/mph.0b013e3182830c25
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thrombocytopenia in a Child Secondary to Passive Platelet Antibody Transfer from a Plasma Transfusion

Abstract: Though rare, passive transfer of platelet antibodies through blood products can result in thrombocytopenia, acute transfusion reactions and death. We report a case of severe alloimmune thrombocytopenia from a plasma transfusion. A post-liver transplant patient with a normal platelet count received fresh frozen plasma (FFP) prior to liver biopsy. Post-biopsy she developed cardiorespiratory distress, petechiae and severe thrombocytopenia (platelet count 2,000/μL). Her platelet count recovered to normal over one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thrombocytopenia secondary to passive transfer of anti‐platelet antibodies is a rare blood transfusion complication (Swain et al , ). All published cases involved passive transfer of anti‐HPA antibodies, with anti‐HPA‐1a antibodies reported in almost all cases (Pavenski et al , ; Collins et al , ; Swain et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia secondary to passive transfer of anti‐platelet antibodies is a rare blood transfusion complication (Swain et al , ). All published cases involved passive transfer of anti‐HPA antibodies, with anti‐HPA‐1a antibodies reported in almost all cases (Pavenski et al , ; Collins et al , ; Swain et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review performed by Pavenski et al (2008) identified 19 reports of passive alloimmune thrombocytopenia; all of these cases were associated with female blood donors with a history of pregnancy (Pavenski et al 2008). Subsequent to this review, another case involving a female donor has been published (Collins et al, 2013). Lookback processes (including in our case) have identified additional patients developing severe thrombocytopenia post-transfusion of blood components from the same donor -suggesting that this diagnosis may be under-recognised (Solenthalar et al, 1999).…”
mentioning
confidence: 76%
“…). Subsequent to this review, another case involving a female donor has been published (Collins et al, ). Lookback processes (including in our case) have identified additional patients developing severe thrombocytopenia post‐transfusion of blood components from the same donor – suggesting that this diagnosis may be under‐recognised (Solenthalar et al, ).…”
mentioning
confidence: 99%